2021
DOI: 10.3390/healthcare9111560
|View full text |Cite
|
Sign up to set email alerts
|

The Aftermath of the COVID-19 Crisis in Saudi Arabia: Respiratory Rehabilitation Recommendations by Physical Therapists

Abstract: Since late 2019, the number of COVID-19 patients has gradually increased in certain regions as consecutive waves of infections hit countries. Whenever this wave hits the corresponding areas, the entire healthcare system must respond quickly to curb the diseases, morbidities, and mortalities in intensive care settings. The healthcare team involved in COVID-19 patients’ care must work tirelessly without having breaks. Our understanding of COVID-19 is limited as new challenges emerge with new COVID-19 variants ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Moreover, as our participants are graduate level and above in the healthcare profession, they are bound to have more knowledge about the disease. There was a positive correlation between the knowledge of COVID-19 and the participant’s educational status, which was similar to that reported in other international studies [ 1 , 2 , 4 , 7 , 8 , 10 , 11 , 12 , 13 , 16 , 17 , 18 , 21 , 25 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In addition to mass media, our participants also reported that scientific journals were a major source of information about COVID-19.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, as our participants are graduate level and above in the healthcare profession, they are bound to have more knowledge about the disease. There was a positive correlation between the knowledge of COVID-19 and the participant’s educational status, which was similar to that reported in other international studies [ 1 , 2 , 4 , 7 , 8 , 10 , 11 , 12 , 13 , 16 , 17 , 18 , 21 , 25 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In addition to mass media, our participants also reported that scientific journals were a major source of information about COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…The physical therapy profession has been known to be one of the essential healthcare professions in improving patients’ health and function at all times. A physical therapist can help COVID-19 patients improve their respiratory functions, exercise endurance, and overall body strength [ 11 , 12 ]. However, since the pandemic began, physical therapy services ceased because COVID-19 can be transmitted from unrecognized COVID-19-infected patients to physical therapists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost in all world regions, COVID-19 necessitated wearing facemasks to the general population, at least between 2020 and 2022 [ 1 , 4 ]. However, wearing facemasks has not been, and never would be, a uniform experience across nations due to cultural, gender, social, economic, and geopolitical forces [ 4 , 5 ]. Indeed, the COVID-19 pandemic has exposed and exacerbated multiple strands of inequalities worldwide [ 6 , 7 ], including in Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…Negligent hiring, training, supervision, and retention by the employer are considered the main factors for negligence at the workplace during this pandemic. Along with WMSDs, many physiotherapists contracted COVID-19 during the care of affected patients [11]. Another factor that needs consideration is that many physiotherapists had to choose the option to work from home and use teleconferencing to manage patients.…”
Section: Introductionmentioning
confidence: 99%